2012
DOI: 10.5539/ijps.v4n3p104
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Art-Making in Recovery, Change, and Self-Understanding---An Interpretative Phenomenological Analysis of Interviews with Everyday Creative People

Abstract: Most creativity theorists consider artists as "agents of control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Beyond the immediate processing components, there are other, long-term outputs that appear under-represented—notably art's role in general well-being or health. As noted by Stevenson-Taylor and Mansell ( 2012 , p. 105), “seldom is a rigorous exploration given to ascertaining the effects of psychological change in the long-term. When and how these changes occur is rarely addressed.” This does certainly seem to be the case here.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the immediate processing components, there are other, long-term outputs that appear under-represented—notably art's role in general well-being or health. As noted by Stevenson-Taylor and Mansell ( 2012 , p. 105), “seldom is a rigorous exploration given to ascertaining the effects of psychological change in the long-term. When and how these changes occur is rarely addressed.” This does certainly seem to be the case here.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with PCT, a number of these studies identified conflict among various important goals that they held for example: a sense of identity, to be socially accepted, and to avoid negative emotions (Alsawy & Mansell, 2013;Stevenson-Taylor & Mansell, 2012). Also consistent with PCT, many participants described that they had less awareness of their goal conflict during their peak distress.…”
Section: Empirical Work On a Pct Approach To Psychological Distress Amentioning
confidence: 90%
“…Qualitative methods are appropriate for discovery-oriented research (Pope & Mays, 2006) and were considered suitable by the authors of these studies as there previously had been little knowledge of the mechanism underlying how recovery occurs. The majority of these studies addressed a mixed range of presenting mental health problems, and they assessed the impact of therapy Higginson & Mansell, 2008;McEvoy, Schauman, Mansell, & Morris, 2012), natural recovery from problematic eating (Alsawy & Mansell, 2013), and the use of art-making within natural recovery (Stevenson-Taylor & Mansell, 2012).…”
Section: Empirical Work On a Pct Approach To Psychological Distress Amentioning
confidence: 99%
“…Thus, a semi-structured interview schedule that includes open-ended questions, prompts, and potential follow-up questions to explore the research questions in depth has been developed. Researcher guided by (Rapley, 2001;Matarazzo et al, 1965;Andrews, 2019;Stevenson-Taylor and Mansell, 2012;Creswell, 2007;Creswell, 2009) , researcher engaging in active listening throughout the interview, demonstrating attentiveness and providing prompts or probes to encourage elaboration and clarification. Semi-structured interviewing offers flexibility to adapt to participants' responses (Creswell, 2009) and delve into emerging themes, facilitating in-depth exploration of their experiences (Rapley, 2001).…”
Section: Data Collectionmentioning
confidence: 99%